A study of consumers' awareness and motivation on Islamic banking / Komala Veeriah - Veeriah, Komala (2012)
Islamic Banking has established in Malaysia for about 29 years. Currently, Malaysia is in aggressive mission to promote Islamic Banking in the international market. However, some argues that Islamic Banking in Malaysia do not receive a satisfactory support and participation from the public mainly due to poor awareness on Islamic Banking products and services, misconception against Islamic Banking system and lack in terms of brand recognition. This study seeks to explore the consumers’ awareness on Islamic Banking products, perspectives on Islamic Banking as well as perception on service brand equity. The findings of this study revealed that awareness and perspectives on Islamic Banking system and its’ products are lacking. This study reveals that religion is the main focus as there is significant differences for all the aspects studied – perspectives, awareness and service brand equity. This study also discovers important dimensions for Islamic Banking service brand development namely employees, environment, service satisfaction, bank operation and bank features. In addition, the relationship between service brand equity and service satisfaction is also investigated and it reveals that 65% of the service brand equity dimensions predicted service satisfaction and the strong contributors being brand personality, aroused feelings, environment, employees, bank operation and self brand image. The findings of this study will provide a holistic and comprehensive marketing insight to improve and strengthen Islamic Banking as well have implications for Islamic Banking management, marketing and branding managers.